If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + -3b = 12 Combine like terms: -3b + -3b = -6b -6b = 12 Solving -6b = 12 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-6'. b = -2 Simplifying b = -2
| 4y+3x=11 | | -13y-26=7y+22 | | 8x+20=5x+35 | | 3x-7y+6z=5 | | X^8=1/12 | | 16/5x=1/10 | | x-5y=-2 | | 9=2w+5 | | -8n-3=-27 | | 3(3x-3)-28=4x-2 | | 3/2*(1-4x)^1/2=-30 | | (((3x-1/4)^2))^4 | | 5x-12=10-6x | | FxD=F | | 11/2*31/2*23/4 | | 4=-6+x | | A+C=A | | 6+9=3x | | -30=3r | | 38=7b+10 | | 2(x-1)=10(1-x)+6 | | 3xy+4xy-xy= | | 4x+29=5-8(x+6) | | 25x^2-36=o | | 6(5y-1)=-2y-38 | | 2+4r=5+4r | | X*7-4x=19-2x | | 90=-6(1+8q) | | 1-5m+3m=3 | | -x^3-6x^2+36x+216=0 | | -8-3(w+13)=4(w+11)-7w | | 15=5/6c |